APLIKASI SISTEM PAKAR MULTI PLATFORM - wawan nurmansyah; Ria Triayomi; Marcelius Michael Livinus (JSR : Jaringan Sistem Informasi Robotik, 2022)
The hardware, software and network base technology continues to evolve. The ease of accessing a system is certainly supported by existing communication technology and cannot be separated from the application of programming languages that have sprung up to support multi-platform systems. Internet of Things-based applications have certainly developed a lot at this time and many are developing the system and its users. Applications that can be used on several operating systems (multi-platform) can be an indicator of the development of applications that are still used on a single platform. An expert system application that was built first on an underweb basis and developed with a mobile device then from the results of this study the use of databases simultaneously from two different platforms. The use of clinical psychology counseling applications using smartphones and computers using underweb can access the knowledge database simultaneously and the results of the consultation history on each platform can be viewed again. Keywords: platform, application, underweb, mobile Â